THE ACTUALIZATION OF SPIRITUALITY AND INTELLECTUALITY OF MUSLIM WOMEN IN THE THOUSAND OF MOSQUE ISLAND (LOMBOK) - Azizah, Lutfatul; Jannah, Miftahul (Center of Gender Studies and Child of State Islamic Institute of Metro, 2022)
‘Pulau Seribu Masjid’ is the name for the island of Lombok which represents a high level of religiosity due to the supports of lots of spiritual sets such as mosques, Islamic boarding schools and many others. Lombok as the religious intellectuality island, it’s obvious seen from the majority of Muslims and lots of achievements in the field of religion. Moreover, the adequate number of Islamic boarding schools and places of public worship is another point term of increasing religious spirituality and intellectuality. The achievements of this large device are also not inferior in number and quality. However, at this high point, the vision of social justice for all of nature (including social justice for Muslims and Muslim women) which is championed by the noble ideals of Islam still requires a more progressive perspective. Along with these achievements, various problems also emerged, one of which was the inequality of space for the actualization of Muslim spirituality and intellectuality, both in the family and in the public sphere. The forms of inequality are the zero representation of women scholars on the Thousand Mosques Island. So this study finds that access to space for increasing the spirituality and intellectual capacity of Muslims and Muslim women is the same but the actualization of spirituality and religious intellectuality is unequal. So it is considered strange for women to lead prayers after congregational prayers even though it is a space that can be accessed by both Muslims and Muslim women.